2017
DOI: 10.1200/jco.2017.35.15_suppl.e12117
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of capecitabine with radiation therapy and survival in breast cancer (BC) after neoadjuvant chemotherapy.

Abstract: e12117 Background: Capecitabine has been studied as a radiosensitizer in rectal cancer, but its role in BC is unclear. Our study seeks to examine the association of concurrent capecitabine/radiation therapy (RT) on survival in women with BC and residual disease after neoadjuvant chemotherapy (NAC). Methods: In a retrospective study of women with stage I-III BC who received Adriamycin/Taxane-based NAC from 2010-2016, we identified 21 women administered concurrent capecitabine/RT. To assess differences in survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many chemotherapy agents used for the treatment of breast cancer work by inhibiting the synthesis of DNA or its precursors, including fluorinated pyrimidine analogs such as gemcitabine and 5-fluorouracil or the purine nucleoside antimetabolite cordycepin. 5 Preclinical studies with gemcitabine showed efficacy as radiosensitizing strategy in both wild-type and p53 mutant MCF-7 cells 6 (although initial results from others were mixed), 7 and have led to clinical trials with gemcitabine 8 and capecitabine 9,10 (ClinicalTrials.gov identifier: NCT03958721) in combination with RT. These pivotal studies were some of the first to demonstrate the value of combination chemotherapy and RT in breast cancer, which has led to an increased interest in the potential use of other chemotherapeutic agents with concurrent RT.…”
Section: Cytotoxic Chemotherapiesmentioning
confidence: 99%
“…Many chemotherapy agents used for the treatment of breast cancer work by inhibiting the synthesis of DNA or its precursors, including fluorinated pyrimidine analogs such as gemcitabine and 5-fluorouracil or the purine nucleoside antimetabolite cordycepin. 5 Preclinical studies with gemcitabine showed efficacy as radiosensitizing strategy in both wild-type and p53 mutant MCF-7 cells 6 (although initial results from others were mixed), 7 and have led to clinical trials with gemcitabine 8 and capecitabine 9,10 (ClinicalTrials.gov identifier: NCT03958721) in combination with RT. These pivotal studies were some of the first to demonstrate the value of combination chemotherapy and RT in breast cancer, which has led to an increased interest in the potential use of other chemotherapeutic agents with concurrent RT.…”
Section: Cytotoxic Chemotherapiesmentioning
confidence: 99%
“…In a retrospective study including 317 patients who received doxorubicin and taxan-based neoadjuvant chemotherapy from 2004 to 2016, Liu et al identified 21 patients receiving adjuvant radiotherapy over 6-8 weeks and simultaneous capecitabine [12]. In all patients, the whole breast and also the lymphatic pathways were included into the radiation fields.…”
Section: Concurrent Usementioning
confidence: 99%